If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3(x+1)=5x-13
We move all terms to the left:
3(x+1)-(5x-13)=0
We multiply parentheses
3x-(5x-13)+3=0
We get rid of parentheses
3x-5x+13+3=0
We add all the numbers together, and all the variables
-2x+16=0
We move all terms containing x to the left, all other terms to the right
-2x=-16
x=-16/-2
x=+8
| 49=12n-11 | | 5r-8=3r+18 | | 4x+2(×+6)=36 | | -10v-6=6v+10 | | 2(3)+10y=6 | | -3(x+2)+13=14-4x | | 3x=2x+50x= | | 4m–8m–-14m–10=-20 | | 225=65+(25+7)n | | 15x=2x+65 | | 2(3x+2)=1/2(12x+8 | | 33+y=70 | | 4y-11=2y+13 | | 19y+34=91 | | 9y-15=4y+20 | | 12.9x+70*125=233*70 | | 11+2x=29 | | 3x^2+72-33x=0 | | -22-x=5+6x=9 | | 5x²+10x+5=0 | | p2+13p+12=0 | | 520+x=603 | | 16x^2+19x-20=0 | | a2-3a-28=0 | | |4x+5|=|−29+-4x| | | 7x-9=12x-36 | | -3x+2-5x−7=4x+2 | | n2+8n+7=0 | | 12.9x-70*125=233*70 | | x-70=74+7x | | 2/9z=18 | | 10x+45=255 |